PENDAMPINGAN INKULTURASI IMAN NATAL MELALUI RITUAL TAPOEN LI’AN OLEF PADA UMAT KAPELA OELNITEP - Ukat, Kristophorus; Binsasi, Frederikus; Pineul, David; Taus, Yohanes Debrito (LPPM STP St. Petrus Keuskupan Atambua, 2026)
Abstract: This article presents a Community Service program focusing on the accompaniment of Christmas faith inculturation through the Tapoen Li’an Olef ritual among the Catholic community of Oelnitep Chapel, Saint John the Baptist Parish Naesleu, within the Atoni Pah Meto cultural context. The program responds to the gap between the liturgical celebration of Christmas and the lived faith experience expressed in local birth rituals. Although Tapoen Li’an Olef continues to be practiced as a cultural tradition, it has rarely been accompanied by explicit Christian theological reflection, limiting its potential as a medium for faith formation. This community engagement aimed to bridge faith and culture through an inculturative pastoral accompaniment integrated into the Advent season and Christmas celebrations. A participatory qualitative approach was employed, including contextual liturgical reflections, symbolic interpretation of ritual elements, interviews with traditional leaders, participatory observation, and the guided enactment of the ritual grounded in Catholic theology. The results indicate increased awareness among the faithful regarding the meaning of Christmas inculturation, greater appreciation of local traditions as legitimate expressions of Christian faith, and active participation across generations. The study affirms that when accompanied reflectively and theologically, the Tapoen Li’an Olef ritual becomes a meaningful space for evangelization, deepens the celebration of Christmas, and strengthens the Church’s identity as rooted in local culture. Key Words: faith inculturation, Christmas, Tapoen Li’an Olef, Atoni Pah Meto culture, community service Abstrak: Artikel ini membahas kegiatan Pengabdian kepada Masyarakat (PkM) berupa pendampingan inkulturasi iman Natal melalui ritual Tapoen Li’an Olef pada umat Kapela Oelnitep, Paroki Santo Yohanes Pemandi Naesleu, dalam konteks budaya Atoni Pah Meto. Latar belakang kegiatan ini adalah adanya jarak antara perayaan Natal sebagai peristiwa liturgis Gereja dan penghayatan iman umat dalam ritual kelahiran yang hidup dalam budaya lokal. Ritual Tapoen Li’an Olef selama ini dijalankan sebagai tradisi adat tanpa pendampingan iman Kristiani yang memadai, sehingga potensinya sebagai sarana penghayatan iman belum tergarap secara optimal. Kegiatan ini bertujuan menjembatani iman dan budaya melalui pendampingan inkulturatif yang terintegrasi dengan masa Adven dan perayaan Natal. Metode yang digunakan adalah pendekatan partisipatif dan kualitatif melalui renungan liturgis kontekstual, refleksi simbol ritual, wawancara tokoh adat, observasi partisipatif serta pelaksanaan ritual yang disertai pendasaran teologis. Hasil kegiatan menunjukkan adanya peningkatan pemahaman umat terhadap makna inkulturasi iman Natal, tumbuhnya sikap apresiatif terhadap tradisi lokal sebagai sarana penghayatan iman serta keterlibatan aktif umat lintas generasi. Kegiatan ini menegaskan bahwa ritual Tapoen Li’an Olef, ketika didampingi secara reflektif dan teologis dapat menjadi ruang pewartaan iman yang kontekstual, memperkaya penghayatan Natal dan memperkuat identitas Gereja yang berakar pada budaya lokal. Kata Kunci: inkulturasi iman, Natal, Tapoen Li’an Olef, budaya Atoni Pah Meto, Pengabdian kepada Masyarakat